HISTORY OF ENGLISH LANGUAGE EDUCATION IN BENGAL UNDER THE BRITISH RAJ: A HISTORICAL ANALYSIS - Abdul Awal (Galaxy International Interdisciplinary Research Journal, 2021)
This study examined the history of English language education in Bengal under British rule (1757-1947). It also investigates the rules of the British to develop the Bengali language too.The British government’s initiative to teach English in Bengal is one of the major parts of the analysis. The impact of different educational policies and commissions in Bengal that were taken by English rulers has been discussed with socio-political examples. The significant contributions of Christian missionaries, as well as local landlords of Bengal, to English education are significantly pointed out. The paper also tries to explore the historical debates in different socio-political and communities about English education in Bengal. It also explains the social and political protests against English learning in Bengal as its consequences.Furthermore, what methods were used in English language teaching in Bengal, are chronologically illustrated. With historical references, the role of females of Bengal in English learning at the time is also examined.